2020
DOI: 10.1089/biores.2019.0050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Menopausal Hormone Therapy on Body Composition and Metabolic Parameters

Abstract: The loss of estrogen with menopause is associated with an increase in central fat. The objective of this study was to evaluate the effects of menopause hormone therapy (HT) on body composition and metabolic parameters in postmenopausal women. A prospective study was conducted among postmenopausal women from the Climacteric clinic, Universidade Federal de São Paulo. Thirty-two participants, median age 51 years, were included. Sixteen women were eligible to receive a low-dose continuous combined HT, containing 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In line with these results, Ahtiainen et al, in a study considering 10 pairs of monozygotic twins, demonstrated that postmenopausal women on HRT (2–10 years) presented a lower waist circumference ( – 6 cm) than their sisters who did not undergo HRT [ 33 ]. More recently, the study by Costa et al in 32 postmenopausal women confirmed that HRT can significantly reduce visceral adipose tissue deposition [ 31 ].…”
Section: Body Composition and Eating Behaviormentioning
confidence: 99%
“…In line with these results, Ahtiainen et al, in a study considering 10 pairs of monozygotic twins, demonstrated that postmenopausal women on HRT (2–10 years) presented a lower waist circumference ( – 6 cm) than their sisters who did not undergo HRT [ 33 ]. More recently, the study by Costa et al in 32 postmenopausal women confirmed that HRT can significantly reduce visceral adipose tissue deposition [ 31 ].…”
Section: Body Composition and Eating Behaviormentioning
confidence: 99%
“… 3 , 4 Indeed, some studies have demonstrated that postmenopausal and older females on estrogen replacement therapy present lower levels of body adiposity, metabolic risk, and inflammation when compared to postmenopausal and older females with no estrogen therapy. 43 , 44 , 45 Collectively, this evidence suggests an important link between estrogen levels with body adiposity, metabolic risk, and inflammation outcomes. Therefore, it is reasonable to assume that postmenopausal and older females may have distinct RT adaptations compared to other populations regarding body adiposity, metabolic risk, and inflammation outcomes.…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, HT use decreases vasomotor symptoms during the menopause transition which can lead to improved sleep, increased activity, and overall increased quality of life, all factors that can further mitigate the changes in body composition experienced during menopause 21 . Additional favorable effects of HT use include an improvement in glucose metabolism, a reduction in the risk of diabetes, an improvement in the lipid profile, a decrease in the incidence of MASLD, and an overall favorable impact on CVD risk 10,16,18,22 …”
mentioning
confidence: 99%
“…21 Additional favorable effects of HT use include an improvement in glucose metabolism, a reduction in the risk of diabetes, an improvement in the lipid profile, a decrease in the incidence of MASLD, and an overall favorable impact on CVD risk. 10,16,18,22 Weight loss can improve cardiometabolic diseases, consequently decreasing CVD and mortality risks. 23 As CVD is the leading cause of mortality in women and menopause is an independent risk factor for CVD, interventions to prevent weight gain and manage overweight and obesity are of particular importance in postmenopausal women.…”
mentioning
confidence: 99%